Constitutional and administrative law - Spencer, Maureen (Nutcases, 2006)
Summarises the basic facts and key principles of the important cases in constitutional and administrative law. Organised by topic areas, this book draws together major themes with additional commentary. This is a revision aid that helps students learn the key cases.